2017
DOI: 10.1002/asia.201701455
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Catalyzed C−H Bond Activation of 5‐Membered Carbocyclic Rings: A Powerful Access to Azulene, Acenaphthylene and Fulvene Derivatives

Abstract: Azulene, acenaphthylene and fulvene derivatives exhibit important physical properties useful in materials chemistry as well as valuable biological properties. Since about two decades ago, the metal-catalyzed functionalization of such compounds, via C-H bond activation of their 5-membered carbocyclic ring, proved to be a very convenient method for the synthesis of a wide variety of azulene, acenaphthylene and fulvene derivatives. For such reactions, there is no need to prefunctionalize the 5-membered carbocycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 82 publications
0
15
0
1
Order By: Relevance
“…Based on these results, we concluded that C−H activation is a very useful method for the functionalization of nonbenzenoid aromatic azulenes. However, no studies on C−H activation using amide directing groups have been described for azulene, a nonbenzenoid aromatic compound [4e,10] . Stimulated by the seminal results of Huang and coworkers [8e,f,g] and our results, [9] we envisioned that the development of C−H activation using azulene‐bearing amide directing groups would be a significant milestone for the expansion of the C−H activation field.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on these results, we concluded that C−H activation is a very useful method for the functionalization of nonbenzenoid aromatic azulenes. However, no studies on C−H activation using amide directing groups have been described for azulene, a nonbenzenoid aromatic compound [4e,10] . Stimulated by the seminal results of Huang and coworkers [8e,f,g] and our results, [9] we envisioned that the development of C−H activation using azulene‐bearing amide directing groups would be a significant milestone for the expansion of the C−H activation field.…”
Section: Methodsmentioning
confidence: 87%
“…Stimulated by the seminal results of Huang and coworkers [8e,f,g] and our results, [9] we envisioned that the development of C−H activation using azulene‐bearing amide directing groups would be a significant milestone for the expansion of the C−H activation field. Although C−H activation has been applied to azulene for its functionalization, these are exclusively done at the 1,3‐position, making use of their natural reactivity [4e] . As far as we know, there has been no attempt to make use of directed C−H activation to overcome the natural reactivity, so as to enable functionalization of azulene at other positions.…”
Section: Methodsmentioning
confidence: 99%
“…Azulene is a special molecule that has a large dipole moment of ≈1.08 D, a narrow HL energy gap, and ion–metal complexing ability. [ 126 ] Because of its distinct chemical structure and properties, considerable research has been conducted on the synthesis of azulene‐based derivatives, including on applications in domains such as near‐infrared absorption, organic FETs, organic solar cells, and MSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its anti‐Kasha‐rule emissions as well as unique structure and photophysical characteristics, azulene has attracted widespread attention. Some recent reviews have summarized the methods for preparation of azulene, [ 21 ] polymeric materials, [ 22 ] and their development in optoelectronics [ 23 ] and electrochromic technology. [ 24 ] Thus, these topics are not discussed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of a methodology employing the so-called late stage C-H bond functionalization allowing the easy access in one step to a wide variety of derivatives of these drugs containing useful functional groups has potential in pharmaceutical chemistry. During the last decades, the metal-catalyzed C-H bond functionalization of a broad range of the sp 2 C-H bonds [5][6][7][8][9][10][11][12][13][14] including cyclic alkenes [15][16][17][18][19][20][21] were demonstrated to be extremely effective for the access to sophisticated structures. With cyclic alkenes, in general the reaction likely proceed via a Heck type mechanism.…”
Section: Introductionmentioning
confidence: 99%